Effect of hand arm vibrational exposure in a Manufacturing Industry - Jinesh Kumar Jain, M.P.Singh (International Journal of Scientific Research and Management (IJSRM), 2013)
Carpal Tunnel Syndrome is a symptomatic compression neuropathy of the median nerve at the level of the wrist/hand characterized physiologically by evidence of increased pressure within the carpal tunnel and decreased function of the nerve at that level. It is characterized by patients as producing numbness, tingling, hand & arm pain and muscle dysfunction. CTS is caused by physical occupational activities, such as repeated and forceful movements of the hand and wrist or use of hand-held, powered, vibratory tools. Present work is focused on studying CTS on the workers engaged in manufacturing industry. The risk factor considered in this study is hand arm vibrational exposure. The study is conducted on 116 workers comprising of all men (mean age of 36.827±5.98 years). The objective of present work is to study the effect of hand arm vibrational exposure on the workers of manufacturing industry by comparison of potential CTS symptoms and effect of different exposure levels of vibration on occurrence of CTS in actual industrial environment.